MACC1 Contributes to the Development of Osteosarcoma Through Regulation of the HGF/c-Met Pathway and Microtubule Stability - Wen, Jia; Xie, Yi; Zhang, Yingqiang; Li, Jiazhen; Li, Jiaping; Zhang, Yan; Lu, Xinchang; Zhang, Yi; Liu, Yongkui; Liu, Tao; Li, Longqing (Frontiers in Cell and Developmental Biology, 2020)
Osteosarcoma (OS) is the most prevalent human bone malignancy, and presents a global annual morbidity of approximately five cases per million. Notably, precise and efficient targeted therapy has become the most promising strategy for the treatment of osteosarcoma; however, there is still an urgent need for the identification of suitable therapeutic targets. Metastasis-associated in colon cancer 1 (MACC1) was first identified in colon tumors by differential display RT-PCR, and was shown to be involved in the regulation of colon tumor growth and metastasis through the hepatocyte growth factor (HGF)/c-Met signaling pathway. Additionally, MACC1 overexpression has been reported to induce the growth of several types of cancers, including glioblastoma multiforme and gastric cancer. However, whether MACC1 also plays a role in the progression of osteosarcoma remains unclear. In this study, we found that MACC1 was highly expressed in human osteosarcoma tissues, as well as in U-2OS and MG-63 cells, when compared with normal tissues and osteoblasts, respectively. Our data further indicated that MACC1 expression was correlated with several clinicopathological features of OS. Through in vitro assays, we found that MACC1 depletion markedly suppressed the proliferative ability of both osteosarcoma cells and endothelial cells, and inhibited the angiogenic capacity of endothelial cells. Similarly, MACC1 depletion inhibited tumor growth, metastasis, and angiogenesis in mice. Mechanistically, we found that MACC1 could bind to the MET promoter, and enhanced the proliferation of both osteosarcoma cells and endothelial cells through the HGF/c-Met signaling pathway. Furthermore, we show that MACC1 also promoted angiogenesis by regulating microtubule dynamics, thereby promoting the progression of osteosarcoma. Our results indicate that MACC1 may be a new and promising therapeutic target for the treatment of osteosarcoma.